Prevalence and management of tuberculosis infection in Apulian rheumatologic patients treated with biologics: An observational cohort 10‐year study from the BIOPURE registry. (12th December 2022) - Fornaro, Marco; Stano, Stefano; Goletti, Delia; Semeraro, Angelo; Cantatore, Francesco Paolo; Maruotti, Nicola; Colella, Sergio; Abbruzzese, Anna; Santo, Leonardo; Praino, Emanuela; Iannone, Florenzo
Abstract: Introduction: The objective of this study was to assess the 10‐year prevalence of latent tuberculosis infection (LTBI) among Apulian patients with rheumatic diseases (RDs). Secondary endpoint was to record new cases of active TB disease and LTBI among patients treated with biologic disease‐modifying antirheumatic drugs (bDMARDs). Methods: We analysed the results from the patients included in the BIOPURE registry from 2009 to 2018, who underwent QuantiFERON‐TB Gold In‐tube (QFT‐GIT) test as screening before bDMARDs treatment. Demographic and clinical data were recorded at the time of the first QFT‐GIT test. Administration of preventive therapy and bDMARD treatments were recorded for patients with positive QFT‐GIT test. All new tuberculosis infections were recorded during the follow‐up. Results: The final study population included 3028 patients (855 rheumatoid arthritis, 1001 psoriatic arthritis, 833 spondyloarthritis, 130 connective tissue diseases, 33 systemic vasculitis and 176 other inflammatory rheumatic conditions), more frequently female (67.2%), with a mean age of 52 ± 18 years. Patients with QFT‐GIT‐positive test were elderly people, predominantly male with higher prevalence of diabetes as comorbidity. The 10‐year prevalence of LTBI was 10.8%. Of note, no cases of TB reactivation were recorded in patients who completed preventive therapy treatment. Three thousand and sixteen patients were followed over time (42.6 ± 30 months), and five (.2%) developed active TB, which corresponds to .47 cases per 1000 person‐years. Conclusions: In the 10‐year observation, the use of bDMARDs seems to be safe in rheumatologic patients with positive QFT‐GIT test treated according to current recommendations. Nevertheless, cases of primary TB disease did occur during treatment with biologicals. Abstract : This study evaluated the prevalence of latent tuberculosis infection (LTBI) in 3028 Apulian patients with rheumatic diseases treated with biologic drugs . The 10‐year prevalence of LTBI was 10.8%. No cases of TB reactivation were recorded when preventive therapy was administered. The use of biologic therapy appears safe despite the occurrence of five cases of primary TB, highlighting the importance of retesting patients with increased risk.